The Reality of Islamic Law Dealing with the Phenomenon of Divorce in the Holy Qur’an: واقعية الشريعة الإسلامية لظاهرة وقوع الطلاق في القرآن الكريم - Sayed Ebrahim, Mahmoud Shaban (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
لم تكن الشريعة الإسلامية أوَّل الشرائع الدينية التي جاءت بالطلاق وتشريعه، ولكن الناظر المتأمل في ذلك يجد أنَّ الشريعة الإسلامية هي أوَّل الشرائع الإسلامية التي جاءت بنظام يكفل لكل من الزوجين حقوقهما، ويحفظ ويصون كرامتهما عند اتخاذ هذه الخطوة التي يشعر من خلالها الزوجين بالمصلحة العامة لهما، وأنَّ الطلاق في هذه الحالة بداية حياة جديدة، وليست نهاية الأمل في الحياة، وقد عنيت الشريعة الإسلامية كشأنها دائمًا في كل ما تقوم به من إصلاح وتقويم للأوضاع الاجتماعية من كل خلل يطرأ عليها، كذلك لم تجعل الشريعة الإسلامية الطلاق أداة للتلاعب بقدسية الزواج، وعدم الاستقرار العام للحياة الزوجية، ولكنها نظَّمت كل ما يتعلق بظاهرة الطلاق، سواء من ناحية الزوج أو من ناحية الزوجة. ومن ذلك تتضح مشكلة الدراسة في زيادة حالات الطلاق ومعدله في الوقت المعاصر، وخاصة في السنوات الأخيرة بشكل لم يكن متعارفًا عليه من قبل، وبشكل يبعث على القلق نحو استقرار الأسرة وتكوينها، ولاسيما إنَّ للطلاق عواقب غير محمودة وآثارًا سلبية على المستويين الفردي والاجتماعي سواء من ناحية الزوج أو الزوجة، أو الأبناء أو على المجتمع بعد ذلك. لذلك تهدف هذه الدراسة إلى بيان وتوضيح واقعية الشريعة الإسلامية لظاهرة وقوع الطلاق في القرآن الكريم، وذلك من خلال ضوابط قرآنية متبعة حرص الإسلام على الالتزام بها، من أجل الاستقرار الأسري، والمحافظة على الأسرة المسلمة من عوامل الانهيار، خاصة في ظل وجود العديد من الأسباب في المجتمعات في عصرنا الحاضر والتي تسهل وقوعه. وتقوم هذه الدراسة على توظيف المنهج الاستقرائي، وذلك في جمع المادة العلمية من خلال الآيات القرآنية، ومن ثمَّ الاستعانة بالمنهج التحليلي من أجل بيان وتوضيح تلك القضية وبيان واقعية الشريعة الإسلامية لهذه الظاهرة. وقد توصلت الدراسة إلى العديد من النتائج التي سعى الباحث في استخلاصها من خلال ما قدمه في منهج موضوعه العلمي وذلك في بيان اهتمام الشريعة الإسلامية بالأسرة، فقضية الطلاق من التكاليف والأحكام الشرعية التي تظهر داخل هذه القضية مظاهر العدل والتيسير في النصوص الدينية التي تُبين أحكام الطلاق في الإسلام، وتوضح من خلال ذلك شمولية الإسلام وواقعيته لقضية الطلاق مع ما يتناسب مع المنطق والواقع، وتراعي واقعية كلٍّ من الزوج والزوجة وكذلك الأولاد والأهل بعد ذلك دون جور أو ظلم لأي جانب من هذه الجوانب. الكلمات المفتاحية: الواقعية, الشريعة, الطلاق, الأسرة. Abstract Although Islamic law was not the first religion law to establish divorce and its regulation, the observer will discover that Islamic law is the first Islamic law to have a system that ensures each spouse’s rights. When taking this step, it retains and maintains their dignity, and the spouses sense the general interest in them, and that divorce in this instance is the beginning of a new life, not the end of hope in life. Similarly, Islamic law did not use divorce to manipulate the sanctity of marriage and the overall instability of married life, but it did govern everything linked to divorce, whether on the side of the husband or the woman. The study’s problem becomes clear in the rise in divorce cases and rates in modern times, particularly in recent years, in a way that was not previously recognized, and in a way that raises concerns about the stability and composition of the family, particularly that divorce has undesirable consequences and negative effects on the individual and social levels, On the one hand, there is the husband or wife, or the children, or the community, and on the other hand, there is the community. Therefore, this study aims to clarify and clarify the reality of Islamic law for the phenomenon of divorce in the Holy Qur’an, through Qur’anic controls followed by Islam’s keenness to adhere to them, for the sake of family stability, and preserving the Muslim family from the factors of collapse, especially in the presence of many reasons in societies in our time that facilitate its occurrence. As a result, the purpose of this research is to clarify and explain the reality of Islamic law for the phenomenon of divorce in the Holy Qur’an, through Qur’anic controls followed by Islam’s eagerness to adhere to them, for the purpose of family stability and protecting the Muslim family against forces of collapse, particularly in light of the many circumstances in today’s society that encourage its occurrence. This study is based on employing the inductive method, in collecting scientific material through the Qur’anic verses, and then using the analytical method in order to clarify and clarify this issue and to clarify the reality of Islamic law for this phenomenon. This research is focusing on utilizing the inductive approach to acquire scientific information from Qur’anic verses, and then using the analytical approach to clarify and explain this problem, as well as the reality of Islamic law in relation to this phenomenon. The study reached many results that the researcher sought to extract from what he presented in the methodology of his scientific subject in explaining the interest of Islamic law in the family. The study yielded several findings that the researcher hoped to derive from what he gave in his scientific subject’s technique in describing the interest of Islamic law in the family. The issue of divorce is one of the costs and legal rulings that appear in this case, the manifestations of justice and facilitation in the religious texts that clarify the provisions of divorce in Islam, and thus clarify the comprehensiveness of Islam and its realism for the issue of divorce with what is commensurate with logic and reality, which in fact considers the realities of the husband and wife, as well as children and parents following This is done without bias or unfairness to any of these factors. Keywords: Realism, Sharia, Divorce, Family